(3YbGFO GdeYJRdIs - (3CHh GdMSf CMeO Hf GdMSjf Hf eMeO Hf CHj HcQ GdQUGU GdUfYGfjs ((3YKeGf Hf Ydi Hf eMeO GdeDPf s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg GdJhGe hCjGOjg GdLSGe s
(3BNQgG (B:s
(3hbGd Udi Gddg Ydjg (B: (3GdYde YdeGf (B: (3Yde HGdbdH gh GdfGaY dc , hYde HGddSGf gh GdMLI Ydjc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJ hJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3Yde GdcdGe (B84) s
Keywords: (3GdJhMjO hGdedd hGdfMds